The Effectiveness of the Drill Method in Improving Short-Serve of Young Badminton Athletes - Mochamad Hafid Rozaqi; Ali Dai Muhammad; Mia Febriana; Eddy Purnomo (PAEDAGOGIA, 2025)
This study examines the urgency of developing short-serve skills in young badminton athletes, responding to critical problems in the form of low accuracy and consistency of serve identified in 65% of U-13 athletes. This phenomenon has a significant impact on competitive performance, considering that short-serve is a fundamental element that determines the early momentum of the match. The investigation used a 2x2 factorial experimental design, involving 32 U-13 male athletes from the Sukoharjo badminton club who were selected through purposive sampling. The research subjects were divided into four groups based on exercise methods (mass and distributed) and initial ability levels (high and low). Data collection was carried out using a Fenanlampir short-serve test instrument with a validity of 0.66 and a reliability of 0.70). The Shapiro-Wilk test was used for normality, Levene’s test for homogeneity, and hypothesis testing was conducted using a dependent sample t-test with a 5% significance level. The results indicated significant improvements in both training methods, with massed practice demonstrating higher effectiveness (N-Gain Score 57.81% for high ability and 42.6% for low ability) compared to distributed practice (39.69% and 20.89%). No significant interaction was found between the training method and initial skill level, indicating the universality of the effectiveness of the massed method. These findings contribute to the development of evidence-based training methodologies, with practical implications in the form of recommendations for the implementation of massed methods as a core component of young athlete coaching programs.